PERAN KEPUASAN PELANGGAN MEMEDIASI PENGARUH PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN - Prasada, I Putu Eka Astra; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 7 No 10 (2018)DO - 10.24843/EJMUNUD.2018.v07.i10.p04, 2018)
ABSTRACT   Customer loyalty is a form of customer loyalty to loyal or continue to use products or services from the same company in the future. Obtaining customer loyalty, the company must pay attention to the factors that influence it. One influencing factor is customer satisfaction, customer satisfaction depends on customer perception and expectation. Price greatly affects the quality of goods and purchasing decisions. The purpose of this study is to explain the role of customer satisfaction mediate the perception of price to customer loyalty. This research was conducted on customer of McDonald's product in Denpasar City. The analysis technique used is path analysis. The number of samples used in this study were as many as 120 respondents, with purposive sampling method. The data were collected through questionnaires, interviews, and observations. Based on the results of research conducted, found customer satisfaction is able to mediate the influence of price perceptions on customer loyalty. This is evidenced by the perception of prices have a positive and significant impact on customer loyalty; price perceptions have a positive and significant impact on customer satisfaction; customer satisfaction has a positive and significant impact on customer loyalty; and customer satisfaction acts as a mediating variable between price perceptions and customer loyalty. Keywords: price perception, customer satisfaction, customer loyalty